A Case of Transient Local Anesthetic Induced Bilateral Vocal Cord Palsy. (17th June 2015) - Rafiq, M.; Al-Zoraigi, U.; Alzahrani, S.; Alabdulkarim, Y.
Abstract : We report a rare case of bilateral vocal cord palsy following total thyroidectomy with successful extubation within 12 hours. The patient is a 33-year-old lady who underwent uneventful total thyroidectomy for compressive symptoms. Thirty minutes after extubation, she developed stridor and the flexible laryngoscopy showed bilaterally adducted vocal cords. The patient, thus, was reintubated and after 12 hours she met the extubation parameters and so she was extubated successfully. The repeated flexible laryngoscopy showed normal vocal cords. A review of the literature revealed limited information on this transient condition.